2005
DOI: 10.1007/s00415-005-0712-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological aspects of the neuropathy of neurogastrointestinal encephalomyopathy (MNGIE) in four patients including two with a Charcot–Marie–Tooth presentation

Abstract: We report on four patients with severe polyneuropathy associated with intestinal pseudoobstruction (MNGIE). Three patients presented characteristic supranuclear ophthalmoplegia, and hyperdense signals on T2 weighted cerebral MRI and dystrophic mitochondria in Schwann cells and in endothelial cells in nerve biopsy specimens. Two of these patients had a Charcot-Marie-Tooth (CMT) presentation. All three were heterozygous for a recessively transmitted double substitution in the TP gene: Glu286Lys/Glu289Ala, Asp156… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…In a study on four MNGIE patients two presented with a CMT-like phenotype [80]. Post-mortem studies of nerve specimens revealed severe axonal degeneration associated with segmental abnormalities of the myelin sheath [80]. In another study five MNGIE patients presented with demyelinating PNP [81].…”
Section: Mendelian Peomentioning
confidence: 96%
See 1 more Smart Citation
“…In a study on four MNGIE patients two presented with a CMT-like phenotype [80]. Post-mortem studies of nerve specimens revealed severe axonal degeneration associated with segmental abnormalities of the myelin sheath [80]. In another study five MNGIE patients presented with demyelinating PNP [81].…”
Section: Mendelian Peomentioning
confidence: 96%
“…Nerve conduction studies may reveal mixed axonal and demyelinating PNP. In a study on four MNGIE patients two presented with a CMT-like phenotype [80]. Post-mortem studies of nerve specimens revealed severe axonal degeneration associated with segmental abnormalities of the myelin sheath [80].…”
Section: Mendelian Peomentioning
confidence: 98%
“…Patients have a loss of function mutation in the intron 8 splice acceptor site leading to loss of exon 8 and lower levels of functional TYMP (Wong, 2012). In addition to mitochondrial deficits, attributed to accumulation of thymidine, patients exhibit T 2 hyperintense white matter lesions (Said et al, 2005). It is unclear whether these represent metabolic lesions, or more provocatively, inflammatory lesions secondary to dysregulated blood-brain barrier opening, although the mechanism by which loss of TYMP might lead to white matter lesion formation is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to patients reported so far, however, there was no evidence of PN, which is regarded as a cardinal feature of MNGIE [10] and, at times, mimics the neurophysiological and clinical presentation observed in CIDP or Charcot-Marie-Tooth disease [11,12]. Interestingly, rare cases with incomplete syndrome have been described, including one late-onset patient with normal NCS after 12 years of disease progression [5,13].…”
Section: Discussionmentioning
confidence: 55%